Governing Digital Consumption: The Impact of Materialism on Impulsive Buying with the Mediating Role of PayLater Services among Indonesian Generation Z - Dinda Aulia Rasyid; Mahir Pradana; Tri Indra Wijaksana; Akhsan Saifullah (Dealings Foundation Institute, 2026)
The expansion of buy now pay later payment facilities within e-commerce platforms has increasingly influenced the purchasing patterns of young consumers, especially Generation Z who are highly involved in digital shopping environments. This study aims to examine the relationship between materialism and impulsive buying behavior while also assessing the mediating role of Shopee PayLater usage among Generation Z consumers. A quantitative research design was employed by distributing online questionnaires to Generation Z individuals in Indonesia who have utilized Shopee PayLater, resulting in 50 valid responses. The data were processed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results demonstrate that materialism has a significant influence on both Shopee PayLater usage and impulsive buying behavior. In addition, Shopee PayLater usage also significantly affects impulsive buying behavior. The mediation analysis further indicates that Shopee PayLater usage strengthens the relationship between materialism and impulsive buying behavior. These findings imply that deferred payment features may increase the tendency toward impulsive purchasing among consumers who exhibit stronger materialistic orientations in digital commerce settings.